2004
DOI: 10.3748/wjg.v10.i22.3245
|View full text |Cite
|
Sign up to set email alerts
|

Expression level of wild-type survivin in gastric cancer is an independent predictor of survival

Abstract: Wild-type survivin mRNA expression levels are of important prognostic value and significant participation of survivin-2B and survivin-DeltaEx3 is suggested in gastric cancer development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1
1

Year Published

2004
2004
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 25 publications
0
26
1
1
Order By: Relevance
“…However, survivin-2B expression was significantly decreased in later tumour stage (III þ IV) in comparison with early stage (I þ II) (Krieg et al, 2002;Meng et al, 2004), and inversely correlated with tumour differentiation and invasion (Meng et al, 2004). Interestingly, although Krieg et al (2002) reported that the expression of survivin and survivin-DEx3 remained unchanged in different stages of cancer, Meng et al (2004) showed that the expression level of survivin-DEx3 is inversely correlated with apoptotic index. It was also reported that survivin-2B expression was dominant in benign brain tumours in comparison with the malignant ones (Yamada et al, 2003), and that survivin-DEx3 expression was prominent in comparison with survivin-2B expression in survivin-expressing acute lymphocytic leukaemia (ALL) and chronic lymphocytic leukaemia (CLL) patient bone marrow samples (Nakagawa et al, 2004).…”
Section: Survivin Variants In Tumorigenesismentioning
confidence: 87%
See 3 more Smart Citations
“…However, survivin-2B expression was significantly decreased in later tumour stage (III þ IV) in comparison with early stage (I þ II) (Krieg et al, 2002;Meng et al, 2004), and inversely correlated with tumour differentiation and invasion (Meng et al, 2004). Interestingly, although Krieg et al (2002) reported that the expression of survivin and survivin-DEx3 remained unchanged in different stages of cancer, Meng et al (2004) showed that the expression level of survivin-DEx3 is inversely correlated with apoptotic index. It was also reported that survivin-2B expression was dominant in benign brain tumours in comparison with the malignant ones (Yamada et al, 2003), and that survivin-DEx3 expression was prominent in comparison with survivin-2B expression in survivin-expressing acute lymphocytic leukaemia (ALL) and chronic lymphocytic leukaemia (CLL) patient bone marrow samples (Nakagawa et al, 2004).…”
Section: Survivin Variants In Tumorigenesismentioning
confidence: 87%
“…In renal cell carcinomas (RCC), while the expression levels of survivin and survivin-DEx3 did not show a decrease in late tumour stages in comparison with the early and intermediate tumour stages in 57 clinical RCC samples, survivin-2B expression was significantly decreased in late tumour stages (Mahotka et al, 2002a), indicating a possible unfavourable role of survivin-2B in cancer development. In gastric cancer, the expression of survivin-DEx3, survivin-2B, and survivin (dominant transcript) was found in cancer tissues, irrespective of their histological type, grade, or stage (Krieg et al, 2002) (Meng et al, 2004). However, survivin-2B expression was significantly decreased in later tumour stage (III þ IV) in comparison with early stage (I þ II) (Krieg et al, 2002;Meng et al, 2004), and inversely correlated with tumour differentiation and invasion (Meng et al, 2004).…”
Section: Survivin Variants In Tumorigenesismentioning
confidence: 96%
See 2 more Smart Citations
“…Previous clinical studies have reported the survivin expression to be associated with tumour cell proliferation, apoptotic inhibition, and a poor prognosis in various human cancers, including NSCLCs (Martinez et al, 2004;Shinohara et al, 2005). However, only a few clinical reports studied these splice variants of survivin in human cancers (Mahotka et al, 2002a;Meng et al, 2004;Ling et al, 2005;Taubert et al, 2005). Therefore, to clarify the clinical significance of these splice variants of survivin in NSCLCs, we performed the present study on the gene expressions of wild-type survivin, survivin-2B, and survivin-deltaEx3 in relation to the subcellular localisation of survivin proteins, tumour cell proliferation, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%